Implementasi Sistem Reward Kinerja Guru di Smp IT Izzuddin Palembang - Puji Rahayu, Tria; Ibrahim, Ibrahim; Niswah, Choirun (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyze the implementation of the teacher performance reward system at SMP IT Izuddin Palembang. The research employs a qualitative method with a descriptive approach. The study involved 11 informants selected using purposive sampling techniques. Data collection methods included interviews, observations, and documentation. Data analysis techniques consisted of data collection, presentation, verification, and conclusion drawing, with data validity tested through triangulation. The analysis results indicate that the implementation of the teacher performance reward system at SMP IT Izzuddin Palembang is carried out through a structured process, starting from data collection, evaluation and selection, determination of reward recipients, to the awarding phase. Each step is carried out objectively and transparently, involving various stakeholders such as the principal, the HR team, and the HR director to ensure fairness and accountability. This system aims to reward high-performing teachers, encourage increased professionalism, and foster a healthy, productive, and competitive work environment in the field of education.